Banging heads onboard buses: Assessment scheme to improve injury mitigation for bus passengers. (12th June 2019) - Edwards, Mervyn; Edwards, Alix; Appleby, Josh; Beaumont, Dean
Abstract: Objective: Although bus travel is one of the safest modes of transport, a substantial number of bus passengers in London are still injured in collision and harsh maneuver incidents, in particular emergency braking. It is not well understood how these passengers are injured. The objective was to better understand the injury mechanisms and develop countermeasures with a test and assessment procedure to prevent or mitigate these injuries. Methods: The UK national STATS19 data were used to determine the size of the problem. Data, including CCTV footage, in combination with inspection of current buses, were used to determine injury mechanisms and identify features and areas in buses associated with more injuries. An assessment system based on visual inspection was developed to encourage a reduction in the number of features associated with injury. Results: The STATS19 analysis showed that three quarters of all injured casualties occurred in incidents where there was no impact, with this proportion rising for seriously injured casualties. Overrepresentation of older females was also seen. The CCTV analysis and bus examinations highlighted issues with poorly positioned handrails, lack of compartmentalization (restraint), and objects with sharp edges and corners. It also showed that a much higher proportion of passengers seated in the area close to the middle doors and wheelchair area were injured compared to other areas of the bus. Factors contributing to this result were that this area contained more features associated with injury and that persons with reduced mobility have greater exposure in this area; that is, more vulnerable passengers currently sit in the less safe areas of the bus. Conclusions: A novel analysis of CCTV footage has enabled a better understanding of injury mechanisms for bus passengers to be developed. In combination with inspection of current buses, this has been used to develop an assessment system to improve the safety of buses in London.